ANALISIS DAN STRATEGI MENINGKATKAN KEPUASAN MAHASISWA IPB TERHADAP PENYELENGGARAAN ASRAMA TINGKAT PERSIAPAN BERSAMA (TPB) IPB - Andhika Safaat; Diah Krisnatuti Pranadji; Megawati Simanjuntak (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2008)
Consumer is the determinant factor for the quality of services. Students as the stakeholder of Bogor Agricultural University (IPB) need to receive the best services. The aimed of this research were to analyze students’ satisfaction on dormitory in Bogor Agricultural University (IPB) and to identify strategy to improve students’ satisfaction. The design of this research was cross sectional study, which carried out in IPB campus, Darmaga-Bogor, West Java for six months since September 2006 to February 2007. Numbers of samples were 289 students. The result showed that the attributes needed to be improved at man’s dormitory were bath room, water availability, the adjustment program for new students, the material construction of dormitory program, the activity of dormitory program, the access to complaint, the dormitory management, the waste management, the safety at room, the tasteof food at canteen, the menu variation, the nutrition of food, the price of food at canteen, the hygiene of food at canteen, and the cleanliness at canteen. Meanwhile, at women dormitory the main priorities to be improved were bathroom, water availability, the place to iron, dispenser, the license for being late, the night’s alarm, the adjustment program, the material construction of dormitory, the activity of dormitory program, the place for complaint, the waste management, the safety at room, the taste of food at canteen, the menu variation, the hygiene of food and the cleanliness at canteen.